Effect of a digital application on knowledge, treatment adherence, and blood pressure control in hypertensive patients: a quasi-experimental study - Hermansyah, Hermansyah; Septiyanti; Wulandari, Dwi; Lestari Handayani, Tri; Rusca Putra, Kuswantoro (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: The prevalence of hypertension increases annually, posing a significant public health concern. Digital health applications have emerged as potential tools to support hypertension management; however, most existing applications lack features that provide adequate information and education to patients. Objective: To evaluate the effect of a digital application on patients’ knowledge, treatment adherence, and blood pressure control in hypertensive patients. Methods: A quasi-experimental study with a pre-test and post-test design and control group was conducted in 2024. Sixty respondents diagnosed with hypertension were selected through purposive sampling and divided equally into intervention (n = 30) and control (n = 30) groups. The intervention group received access to a custom-developed digital application, while the control group received standard care. Data were analysed using the Mann–Whitney test. Results: The results showed that the use of the digital application significantly increased knowledge, improved adherence, and reduced blood pressure among hypertensive patients (p = 0.013). Conclusion: The digital application had a positive and statistically significant effect on patients’ knowledge, treatment adherence, and blood pressure control, indicating its potential as a supportive tool for hypertension management in primary health care.